Back Cover: Optimized Self‐Templating Synthesis Method for Highly Crystalline Hollow Cu2O Nanoboxes (Small Methods 12/2020). Issue 12 (3rd December 2020) - Dai, Ruoyun; Cheong, Weng‐Chon; Jiao, Jiqing; Zhang, Chao; Zhang, Yu; Chen, Zheng; Nan, Caiyun; Chen, Chen
Abstract : In article number 2000521 by Zheng Chen, Chen Chen, and co‐workers, an optimized self‐templating synthesis method is developed for preparing highly crystalline hollow Cu2 O nanoboxes with relatively small sizes. The evolution process is systematically characterized and the synthesis conditions are carefully controlled. Benefiting from the unique hollow structure, Cu2 O nanoboxes can give ≈100% yield for the oxidative homocoupling reaction of terminal alkynes as heterogeneous catalysts under mild conditions.